Post-traumatic stress reactions in a long-term and several generation perspectives - Smith-Solbakken, Marie; Wallin Weihe, Hans-Jørgen (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2018)
The article presents issues related to post-traumatic stress in a social context. The focus was on showing how historical traumas as well as living in the state of fear for a long time affect identity formation of future generations. The exploration was based, among others, on the historical analysis of two oil rig disasters (Alexander Kielland in 1980 and Piper Alpha in 1988) and war, mainly World War II-based trauma.
Keywords: post-traumatic stress disorder; generational message; trauma; identity